The role of pricing in the marketing mix - Naumko, Tetiana; Kaliuzhna, Yuliia (My University, 2019)
Theinfluenceofpricesonthesuccessandcompetitivenessoforganizations, aswellasthechoiceoftheaveragebuyerforone or another productisconsidered.
Keywords: ціноутворення; маркетинг; стратегії ціноутворення; ціна; попит; пропозиція; pricing; marketing; price; pricing strategies; demand; supply; кафедра ділової іноземної мови та міжнародної комунікації